DiaDigital, Apps und digitale Gesundheitsanwendungen: Resümee nach 5 Jahren und wie weiter? - Heinemann, Lutz (Diabetologe, 2020)
The COVID pandemic has given a massive boost to the use of digital options in the care of patients with diabetes. In Germany a good structure for patient care was already established before the pandemic and this structure was able to react remarkably quickly to the challenge. The future will show whether this development can be regarded as established with respect to the use of telemedicine, on-line training etc. The quality of communication between patients and the diabetologist/diabetes team can be sufficient with good IT equipment. The digital approaches and projects discussed in this article, e.g. apps and their evaluation, digital health applications and virtual care of patients between the visits, have prepared the ground for this development in recent years, supported also by the significant changes in health policy on these topics. The digital options that are already available and those that are likely to become available in the foreseeable future will continue to ensure good and safe patient care and are likely to significantly improve it.